Effectiveness of ex ante honesty oaths in reducing dishonesty depends on content - Zickfeld, Janis H; Ścigała, Karolina A; Elbæk, Christian T; Michael, John; Tønnesen, Mathilde H; Levy, Gabriel; Ayal, Shahar; Thielmann, Isabel; Nockur, Laila; Peer, Eyal; Capraro, Valerio; Barkan, Rachel; et al. (Nature human behaviour, 2025)
Dishonest behaviours such as tax evasion impose significant societal costs. Ex ante honesty oaths-commitments to honesty before action-have been proposed as interventions to counteract dishonest behaviour, but the heterogeneity in findings across operationalizations calls their effectiveness into question. We tested 21 honesty oaths (including a baseline oath)-proposed, evaluated and selected by 44 expert researchers-and a no-oath condition in a megastudy involving 21,506 UK and US participants from Prolific.com who played an incentivized tax evasion game online. Of the 21 interventions, 10 significantly improved tax compliance by 4.5 to 8.5 percentage points, with the most successful nearly halving tax evasion. Limited evidence for moderators was found. Experts and laypeople failed to predict the most effective interventions, though experts' predictions were more accurate. In conclusion, honesty oaths were effective in curbing dishonesty, but their effectiveness varied depending on content. These findings can help design impactful interventions to curb dishonesty.
Keywords: podvádění; United Kingdom; United States; mužské pohlaví; ženské pohlaví; Spojené království; dospělí; daně; Humans; Adult; Female; Male; Spojené státy americké; Taxes; lidé; Deception